A survey of fintech research and policy discussion - Allen, Franklin,Gu, Xian,Jagtiani, Julapa (Research Department, Federal Reserve Bank of Philadelphia, 2020)
The intersection of finance and technology, known as fintech, has resulted in the dramatic growth of innovations and has changed the entire financial landscape. While fintech has a critical role to play in democratizing credit access to the unbanked and thin-file consumers around the globe, those consumers who are currently well served also turn to fintech for faster services and greater transparency. Fintech, particularly the blockchain, has the potential to be disruptive to financial systems and intermediation. Our aim in this paper is to provide a comprehensive fintech literature survey with relevant research studies and policy discussion around the various aspects of fintech. The topics include marketplace and peer-to-peer lending, credit scoring, alternative data, distributed ledger technologies, blockchain, smart contracts, cryptocurrencies and initial coin offerings, central bank digital currency, robo-advising, quantitative investment and trading strategies, cybersecurity, identity theft, cloud computing, use of big data and artificial intelligence and machine learning, identity and fraud detection, anti-money laundering, Know Your Customers, natural language processing, regtech, insuretech, sandboxes, and fintech regulations
https://ssrn.com/abstract=3622468
Keywords: Graue Literatur; fintech; marketplace lending; P2P; alternative data; DLT; blockchain; robo advisor; regtech; insuretech; cryptocurrencies; ICOs; CBDC; cloud computing; AML; KYC; NLP; fintech regulations